Vensters op een veelkleurig verleden. : De nieuwe historische canon van Limburg (2024) - Dols, Chris; Heemels, Maurice (Publications de la Société Historique et Archéologique dans le Limbourg, 2024)
Windows onto a Multicolored Past. The new historical canon of Limburg (2024)This article examines historical canon formation in the Dutch Province of Limburg by focusing on the ways in which the ‘old’ (2009) and the ‘new’ (2024) historical canons have been crafted.Journalist and historian Paul van der Steen kickstarted the discussion on the matter in 2005, after which Limburgs Geschied- en Oudheidkundig Genootschap (LGOG), one of the key historical and archeological societies active in Limburg, sprang into action and took over the initiative. The emergence of a historical canon on the national level (2006), too, influenced a process in which 52 phenomena, persons, and objects from the past were deemed important for understanding the multifaceted history of the political and sociocultural entity of Limburg from 1867 onwards and of the landscape, towns, villages, and communities in the Meuse-Rhine Region prior to that particular year. In 2020, once again under the influence of a national trend of canon formation, the decision was made within the realm of LGOG to reconsider the 2009 canon in light of both societal and historiographical developments that had recently taken place. It took three years to actually rethink and revise the canon. Much time and effort was invested into an optimisation of the overall balance as far as the dimensions of gender, everyday life including the so-called ‘dark pages’ of history, social (in)equality, and spatial differentiation were concerned, leading to a total of 54 chapters. As argued in this article, five modes of ‘recalibration’ were used to this end: adding brand new chapters (1), merging existing chapters (2), removing existing chapters (3), replacing existing chapters (4), and rewriting existing chapters (5).